Income Inequality and Subjective Well-Being: Toward an Understanding of the Relationship and Its Mechanisms. Issue 6 (July 2018) - Katic, Ivana; Ingram, Paul
Income inequality is emerging as the socioeconomic topic of our era. Yet there is no clear conclusion as to how income inequality affects the most comprehensive human outcome measure, subjective well-being (SWB). This study provides an explanation for the relationship between income inequality and SWB, by delving into its mechanisms, including egalitarian preferences, perceived fairness, social comparison concerns, as well as perceived social mobility. In a rigorous analysis using a large cross-country dataset, and accounting for the nested structure of the data, as well as controlling for a variety of individual and country characteristics, we find that SWB is higher where income inequality is higher. Importantly, we also find support for this relationship being moderated by perceptions of poverty being caused by unfairness, an individual's relative socioeconomic standing, as well as beliefs about hard work leading to success. Our study highlights the dire need for further scholarly attention to income inequality and its complex effects on SWB.